One Health; Operationalizing One Health in the Arctic - Sustainable Development Working Group (SDWG) (Sustainable Development Working Group, 2017)
One Health is a theoretical concept and practical approach for developing and sustaining broad interdisciplinary collaboration - to identify, prevent, and mitigate health risks in humans, animals and the environment. One Health is a particularly well-matched tool to advance the understanding of health threats from the direct and indirect impacts of climate change in the Arctic. As a multidisciplinary approach, One Health strengthens coordination between and among a wide range of scientific disciplines and stakeholder. One Health enhances participatory community-based approaches for identifying and responding to health issues in communities which take into account traditional and local knowledge (TLK).